Ascorbic acid synthesis and metabolism in maize are subject to complex and genotype-dependent feedback regulation during endosperm development - Sanahuja, Georgina; Farré, Gemma; Bassie, Ludovic; Zhu, Changfu; Christou, Paul; Capell, Teresa (Biotechnology journal, 2013)
L-ascorbic acid (vitamin C) is an antioxidant and electron donor whose metabolism in plants is under strict feedback control. The factors that influence L-ascorbic acid accumulation in staple crops are only partially understood. One way to gain insight into the regulation of L-ascorbic acid metabolism is to investigate the endogenous pathways in various genetic backgrounds and characterize their interactions with transgenes encoding relevant enzymes. In an initial step, we investigated the developmental profile of L-ascorbic acid accumulation in the endosperm of three diverse maize genotypes and a transgenic line expressing rice dehydroascorbate reductase, which enhances L-ascorbic acid recycling. We determined the transcript levels of all the key genes in the L-ascorbic acid metabolic pathways as well as the specific levels of ascorbic acid and dehydroascorbate. L-ascorbic acid levels were high 20 days after pollination and declined thereafter. We found significant genotype-dependent variations in the transcript levels of some genes, with particular complexity in the ascorbic acid recycling pathway. Our data will help to elucidate the complex mechanisms underlying the regulation of L-ascorbic acid metabolism in plants, particularly the impact of genetic background on the strict regulation of ascorbic acid metabolism in endosperm cells.